2022
DOI: 10.28948/ngumuh.1161768
|View full text |Cite
|
Sign up to set email alerts
|

Şeker hastalığı teşhisi ve önerilen modellerinin karşılaştırılması

Abstract: Şeker hastalığı insanlarda kan şekeri seviyesinin anormal değerlere ulaştığı kronik bir rahatsızlıktır. Şeker hastalığının erken teşhisi, bu hastalığın sebep olabileceği daha büyük hastalıkların önlenmesi ve gerekli tedavi planlamasının zamanında gerçekleştirilmesi açısından önemlidir. Bu çalışma kapsamında şeker hastalığı çeşitli modeller ile teşhis edilerek, bu problem için kullanılabilecek en uygun model belirlenmeye çalışılmıştır. Çalışmada Lojistik Regresyon, k-En Yakın Komşuluk, CART (Sınıflandırma ve Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Therefore, the mathematical formula of LightGBM is generally similar to the formula of Gradien Boosting algorithms. LightGBM stands out with features such as histogram-based learning and scaled gradient descent [27]. Basically the mathematical equation is:…”
Section: Lightgbmmentioning
confidence: 99%
“…Therefore, the mathematical formula of LightGBM is generally similar to the formula of Gradien Boosting algorithms. LightGBM stands out with features such as histogram-based learning and scaled gradient descent [27]. Basically the mathematical equation is:…”
Section: Lightgbmmentioning
confidence: 99%
“…Research has shown that igneous rock minerals possess some level of reactivity, and their chemical composition is highly similar to fly ash. When finely ground to a certain degree, igneous rock powders exhibit potential hydraulic activity, known as the "volcanic ash effect" [8,9]. However, due to the relatively low content of amorphous SiO 2 in some igneous rock minerals, their hydraulic activity is limited, which is not conducive to the development of cement's later-stage strength.…”
Section: Introductionmentioning
confidence: 99%